A nail through the heart - Hallinan, Timothy (William Morrow, 2007)
Finding himself embracing domestic life in Bangkok in spite of his love for adventurous travel, writer Poke Rafferty has his world thrown into turmoil by a troubled homeless youth, a distraught woman's missing uncle, and a blackmailing thief.